From Mapalus to Cooperatives: Institutional Transformation of Financial Systems and Social Solidarity in the Coastal Fishing Communities of North Minahasa - Jafar N, Muhammad Kamil; Nasaruddin, Resky Purnamasari; Adilang, Ryanto (Kunuz: Journal of Islamic Banking and Finance, 2025)
This study examines the role of fisher cooperatives in North Minahasa’s coastal communities as hybrid socio-economic institutions that integrate market logic with moral, cultural, and ecological values. It explores how four key dimensions, economic, social, cultural, and ecological, interact within cooperative practices, and how the local value of mapalus (Minahasan mutual cooperation) shapes collective ethics and institutional sustainability. Using a qualitative phenomenological approach, data were collected through participant observation, documentation, and in-depth interviews, then analyzed narratively to uncover meaning structures embedded in fishermen’s social actions. The analysis draws upon Islamic moral economy and institutional theory to interpret how values and norms guide cooperative behavior. Findings reveal that fisher cooperatives serve not only as economic entities providing capital, production inputs, and price stability but also as social spaces that cultivate solidarity, trust, and collective learning. The cultural foundation of mapalus reinforces moral accountability and shared welfare, while ecological practices demonstrate adaptive responses to climate change and marine resource conservation. The study concludes that these cooperatives represent a model of community-based Islamic institutional economics that unites efficiency, ethics, and ecological responsibility. Despite its limited scope, this research provides conceptual insights into how Islamic economic principles can be localized within socio-ecological contexts, offering a foundation for further comparative studies on cooperatives, informal finance, and Blue Economy policies in Indonesia.